Ảnh hưởng của hàm lượng clay và điều kiện chế tạo đến một số tính chất của polypropylen/clay nanocompozit - Hoàng, Thái; Kim, Nguyễn Thạc; Anh, Nguyễn Thế (Vietnam Journal of Chemistry, 2014)
Polypropylene (PP)/organic montmorillonite (Org-MMT) nanocomposites were prepared via direct melt compounding in an intermixer in the presence of 1.0wt% anhydride maleic (AM). The influence of Org-MMT content and of preparation conditions on several properties of PP/Org-MMT nanocomposites were investigated with torque moment diagram analysis, mechanical testing and thermal mechanical analysis (TMA). The  mechanical testing results of samples with different contents of Org-MMT showed that in the presence of 1.0wt% AM, the optimal Org-MMT content is 1.0wt%. Namely, the tensile strength and the elongation at break of PP/AM/Org-MMT (100/1/1) nanocomposite were increased 20.47% and ~3.2 times comparing with those of neat PP, respectively. The TMA results has also proved that the nanocomposite containing 1wt% AM and 1wt% Org-MMT expressed the best thermal dimension stability in the temperature range from 120oC to 200oC. We also found that the suitable technological conditions to prepare PP/AM/Org-MMT nanocomposite via direct melt mixing are the mixing temperature at 180oC, the rate of rotor at 50 rounds per minute and the mixing time at 3 minutes